PENGARUH PEMBERIAN ASI TERHADAP KEJADIAN IKTERUS PADA BAYI BARU LAHIR 0- 7 HARI DI UPT PUSKESMAS WATAMPONE TAHUN 2023 - Sumarni, Sumarni; Susilawati, Susilawati; Sriwidyastuti, Sriwidyastuti; Ermawati4, Ermawati (Yayasan Nusantara Hasana Berdikari, 2023)
Jaundice is a disease that is very common in newborn babies, especially within 24 hours after birth. In newborns, it is divided into physiological icterus and pathological icterus. The aim of this research is to determine the effect of breastfeeding on jaundice in newborn babies aged 0 - 7 days at the Watampone Community Health Center UPT in 2023. This research method uses the Accidental Sampling Method which meets the Inclusion criteria. The population of the subjects of this research were all newborn babies at the Watampone Community Health Center UPT, with a sample of 30 people. The results of the analysis using the Chi-Square Statistical Test obtained a p value of (p = 0.004 < 0.05), so it can be concluded that there is an influence of breastfeeding on the incidence of jaundice in newborns 0 - 7 days old at the Watampone Community Health Center UPT.